Hitler's Secret - Clements, Rory (London Zaffre, 2020)
"In the Autumn of 1941, the war is going badly for Britain and its allies. If the tide is going to be turned against Hitler, a new weapon is desperately needed. In Cambridge, brilliant history professor Tom Wilde is asked by an American intelligence officer to help smuggle a mysterious package out of Nazi Germany - something so secret, even Hitler himself doesn't know of its existence. Posing as a German-American industrialist, Wilde soon discovers the shocking truth about the 'package', and why the Nazis will stop at nothing to prevent it leaving Germany. With ruthless killers loyal to Martin Bormann hunting him down, Wilde makes a desperate gamble on an unlikely escape route. But even if he reaches England alive, that will not be the end of his ordeal. Wilde is now convinced that the truth he has discovered must remain hidden, even if it means betraying the country he loves..."--Publisher description.
Keywords: World War--(1939-1945)